The Relationship of Bullying Behavior to Emotional and Behavioral Disorders in Students - Feny, Feny Pebriana; Rahman, Aulia; Warni, Hernida (Java Nursing Journal, 2025)
Background: Bullying is a prevalent issue affecting adolescents' psychological well-being globally. It may contribute to emotional and behavioral disorders, especially during the critical developmental phase of adolescence. Purpose: This study aimed to investigate the relationship between bullying behavior and emotional and behavioral disorders among students at SMPN 18 West Tulang Bawang, Indonesia. Methods: A cross-sectional analytic survey was conducted involving 108 students selected through stratified random sampling. Data were collected using structured questionnaires and analyzed using the Chi-Square test to determine the association between bullying behavior (categorized as frequent or rare) and emotional-behavioral disorders (categorized as normal or abnormal). Results: Among 108 respondents, 58.3% reported frequent bullying behavior, and 25.9% exhibited emotional and behavioral disorders. The analysis showed no statistically significant association between bullying behavior and emotional-behavioral disorders (p = 0.235; OR = 0.697; 95% CI). Most students who reported frequent bullying behavior still fell within the normal emotional-behavioral range. Conclusion: Although bullying remains a frequent occurrence among students, it was not significantly associated with emotional and behavioral disorders in this sample. However, comprehensive intervention strategies addressing not only bullying but also other psychosocial and environmental factors are recommended to promote mental health among adolescents. School-based mental health programs and parental engagement are essential for fostering emotional resilience and reducing harmful behaviors in school environments.